MALIGNANT STRUMA OVARII (KASUS LANGKA) - Adi Arianto; Udadi Sadhana (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2023)
Struma ovarii (SO) are rare and accur in 2-3% of mature ovarian teratomas, most SO cases are benign. Malignant struma ovarii (MSO) is even more rare and occurs in 0,5- 5% of all cases, with the most common histologies identified are papillary and follicular carcinoma, most commonly affect patients in their 4th to 6th decade of life. Due to the rarity of malignant transformation, data about its management are lacking. A 49-years-old woman P2A0 with abdominal pain and pelvic mass, admitted for a hysterectomy and bilateral salpingo-oophorectomy. The left ovary was measured 13x11x5 cm, cystic and partly solid, filled with gelatinous fluid, composed of thyroid follicles with the appearance of "ground glass", "nuclear inclusion" and "nuclear groove", forming a papillifer structure. The diagnostic of MSO is based on histological features include cellular atypia, increased hyperplasia, nuclear pleomorphism, mitotic activity, vascular and/or capsular invasion. To be classified as a MSO, teratoma containing 50% or more thyroid tissue. MSO necessitates surgical staging for ovarian cancer with pelvic washings, total abdominal hysterectomy, bilateral salpingo- oophorectomy, lymph node sampling, total thyroidectomy, and radioactive I-131 ablation. Based on the clinical examination and histopatological examination the patient was diagnosed with MSO (ICD O: 9090/3).